Household Money Demand: The Euro Area Case - Franz Seitz; Julian von Landesberger (Swiss Journal of Economics and Statistics, 2012)
In this paper we analyse household holdings of the monetary aggregate M3 in the euro area from 1991 until 2009. We develop a nominal model with satisfactory economic and statistical properties. The main determinants are a transactions variable, wealth considerations, opportunity costs and uncertainty. The model is robust to different samples considered and a multitude of mis-specification tests. The exercise also provides insights that go beyond the portfolio allocation decision of households. According to our analysis, it is quite apparent that in equilibrium, households jointly determine consumption and broad money holdings both influenced by wealth as well as interest rates.
Keywords: E41; C32; D12; 330; money demand; cointegrated VARs; households